Поединок отражений: роман / Дмитрий Федотов - Федотов Дмитрий Станиславович (Остросюжет, 2012)
Экземпляры: ф7 (20220215) / Инвентарный номер: 62635 / Цена: 30.00 / Сис.шифр: Р2 / Авт.знак: Ф 34 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6